The Egyptian experience in developing the red meat industry - El Saadany S.A. (Filière des viandes rouges dans les pays méditerranéens, 1998)
During the 1960's, the Egyptian government faced a severe shortage in red meat stocks and had to import large amounts of live fattened calves and sheep. The General Organization for Milk and Meat Production (GOMMP) had the task to conduct an integrated project for fattening buffalo calves. The project goal was to protect suckling calves from slaughter at low weight (50-80 kg) and help farmers to fatten their calves for 8-10 months. In return farmers would get a subsidized loan, milk replacer and concentrate feed. Afterwards the GOMMP continued finishing the calves up to 450-500 kg. This policy increased meat production from weaned calves about seven times. This increase accounted for 17 per cent of the red meat production at national level. Total short and medium loans for animal production reached LE 1,356 million in 1990. After a slowing down the same project was resumed, in 1992, under new regulations with dollars US 50 million as a revolving fund.
Séminaire International sur la Filière des Viandes Rouges dans les Pays Méditerranéens, 20-23 Apr 1997, Tunis (Tunisia)